Prothrombotic Changes in Patients with End-Stage Renal Disease and its Relation to Thrombotic Cardiovascular Complication - Enass Abdul Kareem Al-saadi,1 Haithem A Al-Rubaie2 , Raid A Al-Rubaye3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: There is a great risk of cardiovascular disease (CVD) and vascular thrombosis in patients with End-Stage Renal Disease (ESRD). These patients exhibit numerous abnormalities in coagulation, fibrinolytic, inhibitory protein abnormalities in multiple levels. Aim: To assess hypercoagulable changes by measuring the levels of Antithrombin, plasma fibrinogen and FXII activity in patients with ESRD, and to found correlation between and hematological parameters including: Hb level, WBC count, reticulocyte percentage and platelet count. Method: A case control study conducted at Al-Hayat center, Al Karama teaching hospital during the period from the 1 of February to the 30 of October 2014 and 50 patients aged < 60 years of both genders with (ESRD) in addition to 20 apparently healthy controls were included in this study. Results: Patients and controls were matched for age and gender. The mean hemoglobin level, total WBC count, absolute neutrophil count, reticulocyte percentage and platelets count were significantly lower in ESRD patients than controls, P<0.05. The mean values of the coagulation parameters, ProthrombinTtime (PT), Activated Partial Thromboplastin Time (APTT), Plasma Fibrinogen and Factor XII activity were significantly higher in patients than controls. Anti-thrombin activity was significantly lower in patients group than controls, (P<0.001). Cardiovascular complications and vascular thrombosis included Deep Venous Thrombosis( DVT), Cerebro-Vascular-Accident (CVA), Myocardial Infarction (MI), angina or heart failure reported in 62% of the patients. Patients with cardiovascular complication and vascular thrombosis had significantly higher PT, APTT, and factor XII activity, lower anti-thrombin activity as compared to those without cardiovascular complication and vascular thrombosis. Conclusion: (ESRD) patients had coagulation abnormalities render them more liable to have cardiovascular complications and vascular thrombosis.